EKRANISASI NOVEL KE BENTUK FILM RED WHITE & ROYAL BLUE KARYA CASEY MCQUISTON DAN MATTHEW LOPEZ - Nazar Zahira (Nusantara Hasana Journal, 2024)
This research aims to explore the form of ecranization of the novel into the film Red White & Royal Blue by Casey Mcquiston and director Matthew Lopez. The research method used is descriptive qualitative. The data sources for this research are the novel Red White & Royal Blue by Casey Mcquiston and the film Red White & Royal Blue by director Matthew Lopez. Data collection techniques are carried out by reading, watching, recording and sorting data. First, the author read the novel Red White & Royal Blue by Casey Mcquiston and then watched the film Red White And Royal Blue by director Matthew Lopez. Second, the author collects data by recording important parts that will be used as data. Third, the author selects parts of novels and films as data for the ecranization process. Based on the research results, it can be concluded that there are three aspects of the ecranization process. reduction in characters and plot. Additions occur in the characters and changes in variations can be seen in the characterization. Aspects such as shrinking, adding and changing variations are part of the ecranization process. This is caused by differences in imagination between the director and the novel writer as well as to make parts of the story more efficient due to the length of the film.